Hitherto Unknown Solvent and Anion Pairs in Solvation Structures Reveal New Insights into High‐Performance Lithium‐Ion Batteries. Issue 28 (17th August 2022) - Wahyudi, Wandi; Guo, Xianrong; Ladelta, Viko; Tsetseris, Leonidas; Nugraha, Mohamad I.; Lin, Yuanbao; Tung, Vincent; Hadjichristidis, Nikos; Li, Qian; Xu, Kang; Ming, Jun; Anthopoulos, Thomas D.
Abstract: Solvent‐solvent and solvent‐anion pairings in battery electrolytes have been identified for the first time by nuclear magnetic resonance spectroscopy. These hitherto unknown interactions are enabled by the hydrogen bonding induced by the strong Lewis acid Li +, and exist between the electron‐deficient hydrogen ( δ + H) present in the solvent molecules and either other solvent molecules or negatively‐charged anions. Complementary with the well‐established strong but short‐ranged Coulombic interactions between cation and solvent molecules, such weaker but longer‐ranged hydrogen‐bonding casts the formation of an extended liquid structure in electrolytes that is influenced by their components (solvents, additives, salts, and concentration), which in turn dictates the ion transport within bulk electrolytes and across the electrolyte‐electrode interfaces. The discovery of this new inter‐component force completes the picture of how electrolyte components interact and arrange themselves, sets the foundation to design better electrolytes on the fundamental level, and probes battery performances. Abstract : Hitherto unknown interactions of solvent–solvent and solvent‐anion pairs between the lithium‐ion (i.e., Li + ) solvation structures are unveiled for the first time by nuclear magnetic resonance spectroscopy in the battery electrolytes. It has been found that these pairs bridge originally discrete solvation sheaths and lead to the formation of a conjugated solvation network in the electrolytes, which are strongly dependent on the electrolyte components (solvents, additives, salts, and concentration). These findings are significantly important for designing electrolytes on the fundamental level and probing battery performances at a molecular scale.